The Typology of Hadith as the Bayān of the Qur’an and Its Implications for the Reform of Islamic Inheritance Law - Maizuddin, Maizuddin; Chalida, Sri; Hanum, Sarmida; Zulihafnani, Zulihafnani; Nur, Ikhsan (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This paper is a study of the typology of hadith that functions as the bayān (elucidation) of Qur’anic verses and its implications for the reform of Islamic inheritance law. The use of hadith as the bayān of the Qur’an is a common practice of ulema (Muslim scholars) in producing fiqh (Islamic jurisprudence) law. However, certain uses of hadith as the bayān of the Qur’an have also been criticized by scholars. This study is a literature review on hadith viewed as the bayān of the Qur’an, with the primary focus on Islamic inheritance law. Data were collected by means of examining certain hadith used as the bayān of the Qur’an by mufassir (exegete) and fuqaha (Islamic jurists) in carrying out legal istinbath (decision making), especially in cases of inheritance. This study concerns with the studies of the typologies of hadith functioning as the bayān of the Qur’an and their problems that have not been conducted optimally. These studies indicated that certain hadiths used as the bayān of the Qur’an still posed an issue from a methodological point of view. This present study seeks to address three important issues of concern. First, there are three typologies of hadith as the bayān of the Qur’an, namely 1) hadith stated directly by the Prophet as an explanation or a practice of certain verses, 2) hadith stated by the companions of the Prophet as the bayān of a verse, and 3) hadith with no instruction from the Prophet nor indication from the companions as explanations for certain verses, but used as the bayān of certain verses by Islamic jurists. Second, each typology has methodological problems in terms of the context, incompleteness, and hadith occurrence, and the methodological problem has worsened in the last typology. Third, the use of hadith in the third typology as the bayān of the Qur’an in legal istinbath has provided an opportunity for Islamic jurists to renew the Islamic law in the field of inheritance by taking into account the methodological aspect.